(3GdeYGedGJ GdGdcJQhfjI h GdbGfhf GdOhdj GdNGU (B:s (3GdeTcdGJ h GdMdhd (B/s - (3GdYfRj, RjGO Ndja TOGNs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2010)
(3GdYbHGJ GdbGfhfjI aj GdGJaGbjGJ GdOhdjI CeGe GSJNOGe GdhSGFd GdGdcJQhfjI GdeJYdbI HGTQGW GdcJGHI , eOi edGAeI GJaGbjI GdHjY GdOhdj ddHVGFY (B( (3ajfG (B1980) (3ddJWHjb Ydi GdeYGedGJ GdGdcJQhfjI YHQ GdGfJQfjJ, ERGdI GdYbHGJ GdbGfhfjI aj GdGJaGbjGJ GdOhdjI CeGe GSJNOGe GdhSGFd GdGdcJQhfjI, eOi edGAeI bhGYO GdESJfGO, bhGYO GdGSJfGO GdeJYdbI HGdCTNGU, GdeJYdbI HGdGehGd h GdeJYdbI HGdGdJRGeGJ GdJYGbOjI h ZjQ JYGbOjIs
(3HHdjhZQGajG(B: (3U(B.203-208 (3edGMb U(B.141s
Keywords: (3GdGJaGbjGJ GdOhdjIs; (3GdYbhO GdJLGQjI GdOhdjI s; (3GdbGfhf GdOhdjs; (3JLGQI GdcJQhfjIs; (3bhGfjf hCfXeI s